A case of pulmonary cryptococcosis with large pericardial effusion diagnosed using cervical lymph node biopsy. (21st November 2016) - Liu, Xuchun; Jia, Wei; Huang, Shubin; Sun, Gengyun
Abstract: Pulmonary cryptococcosis (PC) is a relatively rare infectious disease. It mainly involves the lungs; however, in some patients, the infection could spread to other parts of the body. PC mostly occurs in patients with immune deficiencies. However, PC infections have been reported in non‐immunocompromised patients. The diagnosis of PC is challenging in patients without immune deficiencies. Here, the case of a 27‐year‐old immunocompetent woman who was diagnosed with PC was report. She had unexplained fever and a history of close contact with poultry feathers. Lesions were observed in the lungs, pleural cavity, pericardium, and cervical lymph nodes. Biopsy of the cervical lymph nodes helped in the pathological diagnosis of PC. She was treated with fluconazole, and the lesions disappeared. They present this case to encourage detailed inquiry of medical history in such patients, improve the diagnostic awareness of clinicians, and help reduce the likelihood of misdiagnosis.